CORRELATION AND PATH ANALYSIS AMONG QUANTITATIVE TRAITS OF FORAGE SORGHUM GROWN IN THE SEMIARID REGION - DA SILVA, CÍNTHIA KAYANE; FLORENTINO DA SILVA, ALEX; SILVA FEITOSA, DARLITON ALEX; NASCIMENTO SANTOS, BARBARA; FERREIRA BISPO, PAULA CRISTINA; ALBUQUERQUE DE OLIVEIRA, TÂMARA REBECCA; FERREIRA DE OLIVEIRA, GUSTAVO HUGO (REVISTA BRASILEIRA DE MILHO E SORGO, 2023)
Forage sorghum (Sorghum bicolor L.) has been grown in diverse climate variations, in warm and dry regions, or in regions with short drought periods. Thus, there is a need to select sorghum genotypes adapted to production systems under drought or rainy irregularities. This study evaluated the direct and indirect correlations among morphophysiological and productive characters of forage sorghum genotypes with Pearson’s correlation and path analysis. The experiment was designed under complete randomized blocks, with 25 treatments (genotypes) and three replicates. Analyzes of phenotypic correlation and the path analysis were done for plant height, panicle length, stem diameter, plant stand, green matter and dry matter yields, stem weight, plant weight, panicle weight, dry matter content, and forage mass. Plant weight presented the most significant direct effect on the forage mass (target variable), contributing to the increase in forage sorghum production. Therefore, heavier plants are more suitable to select forage sorghum genotypes indirectly, aiming to increase forage mass.